Microstructure, mechanical and corrosion properties of nickel superalloy weld metal - Kisasoz, Alptekin; Tumer, Mustafa; Karaaslan, Ahmet (WALTER DE GRUYTER GMBH, 2021)
Inconel 625 alloy is used in aggressive environments at high temperatures such as in petro-chemical applications, in the aeronautical and nuclear energy industries because of its propitious mechanical properties and corrosion resistance. In this study, Inconel 625 samples were joined with ERNiCrMo-3 filler metal using the MIG (metal inert gas) method. Also, the relationship between the microstructure and corrosion properties of the Inconel 625 weld were investigated. The microstructure properties of the weld metal were determined by a light metal microscope (LMM), a scanning electron microscope (SEM) and by energy dispersive spectroscopy (EDS) analysis. Moreover, the corrosion properties of the weld metal and the base material were examined by potentiodynamic polarization tests. The corrosion behavior and parameters of the electrochemical potentiodynamic polarization were determined depending on microstructure properties. Inconel 625 was joined successfully via multipass welding. Moreover, excessive heat input ensured the formation of intermetallic phases. Mechanical and corrosion properties of the weld metal were affected negatively due to the formation of intermetallics.
Keywords: Inconel 625; welding; microstructure; corrosion; AUSTENITIC STAINLESS-STEEL; DISSIMILAR WELDS; ALLOY; RESISTANCE; TEMPERATURE; DEPOSITION; STRENGTH; BEHAVIOR; Materials Science